Eric Robertson, Arp. Painter, Poet, Sculptor 2006. - Hemus, Ruth (Nordlit, 2007)
Gertrude Stein's 1909 extended textual portrait of Picasso at once tries to capture the artist anew, as he has never been rendered before, and resists closure and flatness of meaning. It is multi-faceted, cubist, repetitive but never static, trying to arrive at the essence of the artist, but acknowledging the slipperiness of its objective. In writing a portrait, biography or monograph, the author's challenge is to apprehend a subject and to distil the themes and techniques of his/her life and work, but without reducing that person to a one-dimensional outline. This is especially difficult when the figure is well-known, or at least when some aspect or aspects of that figure are well-known. It is a challenge that Eric Robertson not only faces, but relishes, in Arp: Painter, Poet, Sculptor (Yale University Press, 2006). When he writes that Arp, "seems to have fostered his multiple identity with a quite deliberate disregard for the biographer's task" (p. 3), it is in a spirit of admiration rather than complaint.